Potential Role for Toll-Like Receptor 4 in Mediating Escherichia coli Maltose-Binding Protein Activation of Dendritic Cells - Fernandez, Stefan (American Society for Microbiology, 2007)
The Escherichia coli maltose-binding protein (MBP) is used to increase the stability and solubility of proteins in bacterial protein expression systems and is increasingly being used to facilitate the production and delivery of subunit vaccines against various pathogenic bacteria and viruses. The MBP tag is presumed inert, with minimum effects on the bioactivity of the tagged protein or its biodistribution. However, few studies have characterized the immunological attributes of MBP. Here, we analyze the phenotypic and functional outcomes of MBP-treated dendritic cells (DCs) and show that MBP induces DC activation and production of proinflammatory cytokines (interleukin-1β [IL-1β], IL-6, IL-8, tumor necrosis factor alpha, and IL-12p70) within 24 h and strongly increases Iκβ phosphorylation in treated cells. Interestingly, phosphorylation of Iκβ was largely abrogated by the addition of anti-human Toll-like receptor 4 (TLR4) antibodies, indicating that MBP activates signaling for DC maturation via TLR4. Consistent with this hypothesis, MBP activated the TLR4-expressing cell line 293-hTLR4A but not control cultures to secrete IL-8. The observed data were independent of lipopolysaccharide contamination and support a role for TLR4 in mediating the effects of MBP. These results provide insight into a mechanism by which MBP might enhance immune responses to vaccine fusion proteins.